Five teams fighting for last four spots - new straits times, ajitpal singh (2010)
University Tunku Abdul Rahman(UTAR)recorded back-to-back victories in the Uni College Basketball League(UCBL)at the UPMindoor Basketball Court in Serdang last weekend.